Descrição e notas taxonômicas comparativas das terminálias femininas de espécies de Peckia robineaudesvoidy, 1830 (Diptera, Sarcophagidae) da Amazônia brasileira - CAMARGO, Sofia Lins Leal Xavier de (Universidade Federal do Pará, 2017)
Description and comparative morphological notes of female terminalia of species of Peckia Robienau-Desvoidy, 1830 (Diptera, Sarcophagidae) from the Brazilian Amazon. In order to contribute and allow specific identification of female of the genus Peckia, the terminalia of 15 species that occurs in Brasilian Amazon are described, illustrated and an identification key to females is given. Besides gena color and the presence of setulae in gena and calypter, the shape of spermathecae and tergite 6 can also be used in the subgenus determination. The sternites 6, 7 and 8, the position of spiracle 6 and the microtrichosity of tergite 6 reveled important to specific identification. The tergite 8 is present only in the species Peckia (Pattonella) intermutans (Walker, 1861). The shape of vaginal plate, a structure present only in four species of subgenus Peckia, differs in shape and can be used to characterize these species. Therefore, a combined analysis of these features of female terminalia is necessary in the species determinationof the females of Peckia. Peckia (Peckia) hilifera (Aldrich, 1916) is recorded for the first time from Brazil.